An Analysis of the Artistic Characteristics of Northeast Folk Songs: –takes "Watching the Yangko Dance"as an example - Yang, Lu (Transactions on Social Science, Education and Humanities Research, 2024)
"Watching the Yangko Dance" is a popular, influential and representative northeast folk song, not only lyrics and composition, singing and singing, but also into many northeast Yangko tunes. Taking the northeast folk song " Watching the Yangko Dance" as an example, this paper comprehensively analyzes the artistic characteristics of the northeast folk songs contained behind the works by analyzing the cultural background, the structure of the works, the melody and rhythm characteristics, the singing skills and the stage performance.